2013
DOI: 10.1002/cm.21112
|View full text |Cite
|
Sign up to set email alerts
|

Gelsolin expression increases β1‐integrin affinity and L1210 cell adhesion

Abstract: Integrins are functionally regulated by “inside-out” signaling, in that stimulus-induced signaling pathways act on the intracellular integrin tail to regulate the activity of the receptor on the outside. Both a change in conformation (affinity) and clustering (avidity/valency) of the receptors occurs, but the mechanisms that regulate inside out signaling are not completely understood. Previously, we identified gelsolin in a proteomics screen to identify proteins involved in inside-out control of integrins usin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Our initial in vitro data revealed a decrease in invasiveness and loss of cellular aggregation upon gelsolin depletion in GC cells. This is corroborated by previous reports that gelsolin is required for tumor cell invasion and cellular aggregation in various carcinomas [ 33 , 46 , 47 ]. Since the effect of gelsolin on cellular aggregation is determinant upon the presence of functional E-cadherin, we investigated the possible effects of gelsolin on E-cadherin expression.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our initial in vitro data revealed a decrease in invasiveness and loss of cellular aggregation upon gelsolin depletion in GC cells. This is corroborated by previous reports that gelsolin is required for tumor cell invasion and cellular aggregation in various carcinomas [ 33 , 46 , 47 ]. Since the effect of gelsolin on cellular aggregation is determinant upon the presence of functional E-cadherin, we investigated the possible effects of gelsolin on E-cadherin expression.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, in contrast to its role in invasion and migration, the role of gelsolin in intercellular adhesion is not well studied. Gelsolin was previously reported to interfere with intercellular adhesion in canine kidney cells [ 29 ] and also in the regulation of β1-integrin affinity and cell adhesion in leukemic cells [ 33 ]. In this study we showed that gelsolin inhibits intercellular adhesion in GC cells by regulating the expression of E-cadherin.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16] Recently, it was shown that the protein level of gelsolin, an actin severing and capping protein, affects β 1 -integrin affinity and cell adhesion in the lymphocytic leukemia cell line L1210 and histiocytic lymphoma cell line U937. 17,18 As detected by 2D-gel electrophoresis, adherent growing L1210 cells (L1210-A) with active β 1 -integrins contained an almost 4-fold increase in gelsolin protein level compared with suspension growing L1210 cells (L1210-S) with inactive β 1 -integrins. 18 Further evidence that gelsolin protein levels were related to β 1 -integrin affinity regulation was obtained by modulating the protein levels in L1210 cells.…”
Section: Integrin Affinity Regulationmentioning
confidence: 95%
“…Knockdown of gelsolin in L1210-A cells or ectopic overexpression of gelsolin in L1210-S cells decreased or increased high affinity β 1 -integrins, respectively. 17 The severing and capping activity of gelsolin is controlled by binding of Ca 2+ and PI(4,5)P2. 19 Since gelsolin protein levels by itself affect β 1 -integrin affinity, without the need to stimulate the cells, it was hypothesized that gelsolin has basal activity, which accounts for the necessary actin severing and capping activity in resting cells.…”
Section: Integrin Affinity Regulationmentioning
confidence: 99%
“…Both THBS1 and GSN can directly bind ITGB1 (CD29) . The exosomal integrins have been reported to direct uptake of exosomes by specific organs, where exosomal integrin α6β1 is associated with lung metastasis in a breast cancer model .…”
Section: Top Ev‐derived Proteins Differentially Expressed In Lncap Cementioning
confidence: 99%